2021
DOI: 10.12720/jcm.16.1.8-19
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic-Based Wireless Nano-Sensors Network: Architectures and Applications

Abstract: Recent advances in nano-materials and nanotechnology have paved the way for building integrated devices with a nanometric size, named nano-nodes. These nano-nodes are composed of nano-processor, nano-memory, nano-batteries, nano-transceiver, nano-antenna and nano-sensors, which operate at nano-scale level. They are able to perform simple tasks, such as sensing, computing and actuation. The interconnection between microdevices and nanonodes/nanosensors has enabled the development of a new network standard, call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…By relating the MD structure to the AC signal, see Fig. (1). It is found that the MD structure acts as a molecular diode effectively because it can straighten the AC signal well.…”
Section: Rectification Processmentioning
confidence: 98%
See 1 more Smart Citation
“…By relating the MD structure to the AC signal, see Fig. (1). It is found that the MD structure acts as a molecular diode effectively because it can straighten the AC signal well.…”
Section: Rectification Processmentioning
confidence: 98%
“…Nanotechnology is the treatment of matters on the atomic, molecular, and super-molecular scale. Nanotechnology is attracting increasing investment from both government and industries around the world, providing significant opportunities for the exploration of new emerging Nano devices such as carbon Nanotubes and DNA at the Nano scale [1,2,3]. Molecules and Nano electronics using molecules are monostructures and nanoparticles as the active ingredients produce promising technology concepts that are receiving exponentially increasing interest.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a description of the cutting-edge wireless technology known as LoRa is presented, and a contemporary architecture using LoRa to create an ISM communication network is suggested [26]. Wireless nanosensors have revolutionized traditional methods for addressing a wide range of issues, particularly in the fields of medical, smart environments, farming, and food standards [27]. The several kinds of heat nanosensors, their production processes, and their implementations in diverse industries are all described by Behera et al [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent advances in nanomaterials and nanotechnology have enabled the development of nano-electronic devices. [1] The major advantages of nano-batteries over the micro-batteries are high power density, short charging time, and long shelflife. [2] Nano-batteries have been largely utilized in computer chips, micro-electromechanical systems, electrochemical/optical nanosensors, medical devices which may be inserted in patients for execution targeted diagnostic/ therapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in nanomaterials and nanotechnology have enabled the development of nano‐electronic devices [1] . The major advantages of nano‐batteries over the micro‐batteries are high power density, short charging time, and long shelf‐life [2] .…”
Section: Introductionmentioning
confidence: 99%